2006
DOI: 10.1177/1043659606291549
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to War-Related Traumatic Events, Prevalence of PTSD, and General Psychiatric Morbidity in a Civilian Population From Southern Lebanon

Abstract: The South of Lebanon has experienced prolonged armed conflict. The current study aims to investigate the degree of exposure to traumatic events and prevalence of posttraumatic stress disorder (PTSD) and nonspecific general psychiatric morbidity in a civilian population from the South of Lebanon. The design was cross-sectional with random sampling. War-related traumatic events and symptoms of PTSD were assessed by the Harvard Trauma Questionnaire and general psychiatric morbidity by the General Health Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
100
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 27 publications
(36 reference statements)
13
100
5
Order By: Relevance
“…Th e hypothesis of the study, which predicted that the middle generation of adult children would reported the highest levels of PTSD symptoms, was not confi rmed. However, fi ndings similar to those of the current study have demonstrated that the negative eff ects of war, such as PTSD symptoms, are more common among the elderly population than among the young (Farhood et al 2006;Tang 2007;Trautman et al 2002). Farhood and colleagues (2006) explained this fi nding not in terms of age, but rather in the sheer amount of exposure to number of traumatic events: clearly, the elderly participants have been exposed to more of traumatic events than their off spring.…”
Section: Age and Gender Diff Erencessupporting
confidence: 40%
“…Th e hypothesis of the study, which predicted that the middle generation of adult children would reported the highest levels of PTSD symptoms, was not confi rmed. However, fi ndings similar to those of the current study have demonstrated that the negative eff ects of war, such as PTSD symptoms, are more common among the elderly population than among the young (Farhood et al 2006;Tang 2007;Trautman et al 2002). Farhood and colleagues (2006) explained this fi nding not in terms of age, but rather in the sheer amount of exposure to number of traumatic events: clearly, the elderly participants have been exposed to more of traumatic events than their off spring.…”
Section: Age and Gender Diff Erencessupporting
confidence: 40%
“…Scores on the anxiety subscale of a standard health questionnaire closely correlated with PTSD. The authors concluded that there was a need for psychological interventions among these people as well as research to evaluate the effectiveness of such interventions (12).…”
Section: Vietnam Warmentioning
confidence: 99%
“…For example, Adams & Boscarino [17] found one year after the World Trade Center Attacks (n = 2,368) that proximity to the events, or rather, the more exposed the individual is to the events, the more likely they are to experience more psychological problems. However, the risk factor most associated with the psychological effects of trauma is previous exposure [9,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although community devastations have been studied, the most long-lasting and devastating of community trauma is that caused by war, armed conflict, or mass violence [7]. Studies on the psychological effects of war have been conducted on civilian populations, however, little is still known concerning the effects of continuous armed conflict on civilians residing in volatile areas [5,[8][9][10]. Refugee studies are abundant and have shed light on the experience of civilians during and after conflict in terms of prevalence rates of psychiatric morbidity, risk factors and adjustment [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation